The Effectiveness Of Digital Tools In Developing Translation Skills (Journal of Namibian Studies : History Politics Culture, 2023)
The translation profession has undergone a significant transformation in the 21st century, with the emergence of various digital tools designed to augment the proficiency and productivity of translators. Significantly, the use of these tools has proven to aid translators in acquiring relevant translation skills. As such, this present study investigates the frequency of usage of some of these tools, and the effectiveness of digital tools used in the domain of translation. The study also identified two most important translation skills; which are translation practice skills and post-translation skills. Moreover, the digital tools used for the above identified translation skills were explored, and the views of relevant stakeholders in the translation domain on the use of these tools were investigated. In this study, one-hundred and thirty-three participants, which include professional translators, translation students, and translation tool developers, were randomly selected to offer their varied opinions through an online survey, on the use of digital tools in developing translation skills. Through the use of descriptive-statistics tools, the study presented the views of these participants, capturing the frequencies and percentile values of their responses which form the basis of the data for the research. The data is subjected to statistical analyses in order to identify variations and perspectives. The results of the study provide insight into the advantages and constraints of utilizing digital technologies, such as increased productivity, enhanced control over terminology, prospects for teamwork, and certainty of translation quality, underscoring the significance of human involvement. The results shed light on the possibilities of using digital resources to further develop the two translation capabilities that were identified.